Nucleotide sugar profiles throughout development in wildtype and galt knockout zebrafish. Issue 5 (5th June 2020) - Haskovic, Minela; Coelho, Ana I.; Lindhout, Martijn; Zijlstra, Fokje; Veizaj, Raisa; Vos, Rein; Vanoevelen, Jo M.; Bierau, Jörgen; Lefeber, Dirk J.; Rubio‐Gozalbo, M. Estela
Abstract: Nucleotide sugars (NS) are fundamental molecules in life and play a key role in glycosylation reactions and signal conduction. Several pathways are involved in the synthesis of NS. The Leloir pathway, the main pathway for galactose metabolism, is crucial for production of uridine diphosphate (UDP)‐glucose and UDP‐galactose. The most common metabolic disease affecting this pathway is galactose‐1‐phosphate uridylyltransferase (GALT) deficiency, that despite a lifelong galactose‐restricted diet, often results in chronically debilitating complications. Alterations in the levels of UDP‐sugars leading to galactosylation abnormalities have been hypothesized as a key pathogenic factor. However, UDP‐sugar levels measured in patient cell lines have shown contradictory results. Other NS that might be affected, differences throughout development, as well as tissue specific profiles have not been investigated. Using recently established UHPLC‐MS/MS technology, we studied the complete NS profiles in wildtype and galt knockout zebrafish ( Danio rerio ). Analyses of UDP‐hexoses, UDP‐hexosamines, CMP‐sialic acids, GDP‐fucose, UDP‐glucuronic acid, UDP‐xylose, CDP‐ribitol, and ADP‐ribose profiles at four developmental stages and in tissues (brain and gonads) in wildtype zebrafish revealed variation in NS levels throughout development and differences between examined tissues. More specifically, we found higher levels of CMP‐ N ‐acetylneuraminic acid, GDP‐fucose, UDP‐glucuronic acid, and UDP‐xylose in brain and of CMP‐ N ‐glycolylneuraminic acid in gonads. Analysis of the same NS profiles in galt knockout zebrafish revealed no significant differences from wildtype. Our findings in galt knockout zebrafish, even when challenged with galactose, do not support a role for abnormalities in UDP‐glucose or UDP‐galactose as a key pathogenic factor in GALT deficiency, under the tested conditions. Abstract :